Blockchain Blockchain as a Solution to Overcome the Case of Village Fund Budget Cuts in Indonesia - Muhammad Apriyansyah; Ananda Aditya Saputra; Astriana Mulyani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The village fund budget became the main focus after the many corruption cases in village funds. Village funds have leaked up to 32.2 billion in 2019. This fantastic figure has hindered equity in Indonesia. Net citizens' responses on Twitter to village funds also reap a lot of pros and cons. The author uses data mining management with the nave Bayes method as a form of support action for improving the village crowdfunding system. Nave Bayes itself is one of the methods used to classify netizens' responses to the importance of these responses to assist critics in improving the village crowdfunding system. By using the study research method, the solution to this problem can be overcome by the blockchain method as a solution. This blockchain method has a centralized scheme without a central overseeing it, because this supervision will be supervised by all parties who have joined the blockchain network so that no one party does not oversee the course of transactions. And for the results achieved in this classification data processing, the accuracy of the data reaches 88.10%, the result of the accuracy value is a fairly high result for this study. From these results, it seems that the community, especially netizens on Twitter, are critical of the improvement of the village crowdfunding system. Therefore, with the results obtained from this study research method, namely by creating a decentralized blockchain scheme to prove blockchain records with decentralization can handle cases of village fund corruption.